Inexperienced teachers and knowledgeable others in lesson study: what lessons are drawn from the new practice? - Lisnet Mwadzaangati (Discover Education)
Abstract This study explored how Malawian teachers who participated in an adapted lesson study (LS) professional development (PD) for the first time understood teacher collaboration, and the lessons learnt by the inexperienced knowledgeable other (KOs) through facilitating the new practice. The study was conducted qualitatively using data from lesson plans, lesson planning and lesson reflection sessions. The findings revealed shifts in teachers’ understanding of teacher collaboration from as only meaning division of roles to also including individual and group ownership and mutual support in all phases of LS. The findings further revealed that inexperienced KOs’ challenges in facilitating LS in contexts where LS is not a known practice are greater, probably resulting into gradualness in teachers’ understanding of the LS process and improvement in their teaching. Therefore, while LS is an effective PD for teachers’ learning about improving their teaching, the inexperienced teachers and inexperienced KOs’ understanding of conducting and facilitating this practice may develop over time and with frequent practice. Further research is required to understand how inexperienced KOs can effectively handle different LS issues including teacher resistance.